2020
DOI: 10.1108/caer-06-2019-0103
|View full text |Cite
|
Sign up to set email alerts
|

How country of origin influences Chinese consumers' evaluation of imported milk?

Abstract: PurposeThe purpose of this study is to decompose the effects of country-of-origin labeling (COOL) into multiple dimensions—macrolevel image, related to the country image, and microlevel image, related to dairy industry/product attributes—and investigate how each dimension affects Chinese consumers' evaluation of imported milk.Design/methodology/approachThis study adopted the Becker–DeGroot–Marschak (BDM) auction mechanism to elicit consumers' willingness to pay (WTP) for milk from different countries (New Zeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 89 publications
2
30
0
Order By: Relevance
“…In addition, consumers have an expectation of what the package design should be like and would generally be averse to trying designs that do not match the picture they have in their minds. Zhang et al [ 19 ] reported that the design style or colour of the package of UHT milk was shown to have an influence on consumer attraction. The authors suggested that if consumers are more attracted to the design style or colour, their willingness to purchase will be higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, consumers have an expectation of what the package design should be like and would generally be averse to trying designs that do not match the picture they have in their minds. Zhang et al [ 19 ] reported that the design style or colour of the package of UHT milk was shown to have an influence on consumer attraction. The authors suggested that if consumers are more attracted to the design style or colour, their willingness to purchase will be higher.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that consumers often rely on misleading and inaccurate beliefs when judging packaging for sustainability. Most studies acknowledge how the expectations and responses of consumers vary based on the design (shape, orientation, alignment of graphical forms), branding, visual appearance, colour, verbal claims and quality of products [ 13 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between quality and COOL is strong, particularly for fresh and perishable products (Tsiros and Heilman, 2005). However, the preference is the opposite in emerging or less-developed countries (Ortega et al, 2016;Zhang et al, 2018).…”
Section: Fluid Milkmentioning
confidence: 99%
“…For consumers and companies who want to engage with the ‘buy local’ discourse or express ‘support local’ behaviors, the Standard offers new food label cues to identify and position manufacturer products and supermarket branded products as veritable domestic products. Purchase willingness and evaluations of product images are influenced by the formation of country images (Skaggs et al, 1996; Zhang et al, 2018). Drawing attention to product and ingredient origins can reinforce stereotypical product–country images and ethnocentric buying behavior.…”
Section: Blurred Distinctions Between ‘Domestic’ and ‘Foreign’mentioning
confidence: 99%
“…The demand for Australian milk brands and infant formula in China illustrates the influence of country-of-origin information on consumers’ willingness to pay and their formation of product–country images. Since the melamine-tainted milk scandal in 2008, concerns by Chinese consumers over the safety and quality of domestic dairy products have created a sustained demand for dairy imports (Zhang et al, 2018). In the fast-moving consumer goods sector, which requires low-involvement decisions by consumers, country-of-origin labels are observed to exert a greater influence on purchase behavior than brand knowledge.…”
Section: Globalizing Food Labelsmentioning
confidence: 99%